Genome-Wide Association Studies Reveal All-Stage Rust Resistance Loci in Elite Durum Wheat Genotypes - Aoun, Meriem; Rouse, Matthew N.; Kolmer, James A.; Kumar, Ajay; Elias, Elias M. (Frontiers in Plant Science, 2021)
Leaf rust, caused by Puccinia triticina (Pt), stripe rust caused by Puccinia striiformis f. sp. tritici (Pst), and stem rust caused by Puccinia graminis f. sp. tritici (Pgt) are major diseases to wheat production globally. Host resistance is the most suitable approach to manage these fungal pathogens. We investigated the phenotypic and genotypic structure of resistance to leaf rust, stem rust, and stripe rust pathogen races at the seedling stage in a collection of advanced durum wheat breeding lines and cultivars adapted to Upper Mid-West region of the United States. Phenotypic evaluation showed that the majority of the durum wheat genotypes were susceptible to Pt isolates adapted to durum wheat, whereas all the genotypes were resistant to common wheat type-Pt isolate. The majority of genotypes were resistant to stripe rust and stem rust pathogen races. The durum panel genotyped using Illumina iSelect 90 K wheat SNP assay was used for genome-wide association mapping (GWAS). The GWAS revealed 64 marker-trait associations (MTAs) representing six leaf rust resistance loci located on chromosome arms 2AS, 2AL, 5BS, 6AL, and 6BL. Two of these loci were identified at the positions of Lr52 and Lr64 genes, whereas the remaining loci are most likely novel. A total of 46 MTAs corresponding to four loci located on chromosome arms 1BS, 5BL, and 7BL were associated with stripe rust response. None of these loci correspond to designated stripe rust resistance genes. For stem rust, a total of 260 MTAs, representing 22 loci were identified on chromosome arms 1BL, 2BL, 3AL, 3BL, 4AL, 5AL, 5BL, 6AS, 6AL, 6BL, and 7BL. Four of these loci were located at the positions of known genes/alleles (Sr7b, Sr8155B1, Sr13a, and Sr13b). The discovery of known and novel rust resistance genes and their linked SNPs will help diversify rust resistance in durum wheat.